Archimedes’ Lever - Bloom, Dan (Psychotherapie-Wissenschaft, 2020)
This is a reflection on philosophy and psychotherapy. It develops the notion that the two are so entwined that it is more appropriate to consider the philosophy of psychotherapy, the thinking that is intrinsic in it. The paper proposes that thinking is an engaged and embodied practice of understanding and psychotherapy is its embodied, clinical enactment. Philosophy and psychotherapy, in some sense, began as common human responses to the being-in-the-world, wonder, and disappointment. This idea is discussed from an historical perspective from pre-Socratic philosophy, empiricism, the Kantian, and phenomenology. A central focus is on thinking as implicit in the psychotherapy process.